STUDY ON INITIATIVES OF HIGHER EDUCATION INSTITUTIONS TOWARDS ENTREPRENEURIAL SKILLS DEVELOPMENT - K.R, Girisha; K. S., Sarala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In India, almost all young individuals spend 12 to 15 years in educational institutions, which presents a significant opportunity to cultivate and foster an entrepreneurial attitude among students. Several reports suggest that educational institutions can cultivate entrepreneurial skills through structured curricula and practical experience. In this background, present study aims to examine the steps undertaken by selected 120 higher education institutions in Karnataka considering Government and Private First Grade Colleges in the Tumkur, Bangalore Rural and Chikkaballapura Districts to cultivate entrepreneurial abilities among students across Arts, Commerce and Science students and also to assess students’ perceptions of career options in the business environment.